Repellency Assays with Schinus molle var. areira (L.) (Anacardiaceae) Essential Oils against Blattella germanica L. (Blattodea: Blattellidae) - Sanchez Chopa, Carolina (2009)
Plant extracts have been used all over the world as an alternative method to control pests. In our study, essential oil extracted from leaves and fruits of Schinus molle var. areira (L.) (Anacardiaceae) was tested for repellent activity against adult males of Blattella germanica(L.), in a choice-test arena.  Essential oil was extracted by hydrodistillation. Half of a circular white filter paper of 9 cm diameter was treated with the essential oil and the other half only with the solvent. Each extract was tested at 176, 70 and 35.38 mg/square cm. The activity of the extracts was compared to the standard treatment with N,N-diethyl-m-toluamide (DEET). The essential oil from leaves did not show repellency to B. germanica. The repellency response to S. molle var. areira essential oil from fruits was significantly different from the control at all doses tested. The response of the cockroaches to essential oil from fruit differed significantly from DEET at 70 mg/square cm and 35.38 mg/sqaure cm. Antennectomy of cockroaches resulted in a diminished response to the test compounds.